Disharmonization of executive and legislative relations in 2018 APBA determination - HASAN, E; DANI, M.H (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to determine the factors that cause the conflict between the Executive and the Legislature in determining the fixation of Aceh Provincial Budget. The writer is using Power Relations Theory and the Behavior Approach Theory. The research approach is carried out using descriptive qualitative methods. Results showed that the factors that created conflict between the Executive and Legislative institution regarding the determination of APBA are: conflicts of interest between the Executive and Legislative parties, inconsistent political communication between the Executive and Legislative parties, differences in party ideology, and the absence of the governor in the budget discussion meeting.